THE USE OF GAME TO INCREASE STUDENTS’ VOCABULARY AT SMP KRISTEN MALAK MATUNGKAS - Manurung, Rumindah S.; Samola, Nurmin; Sanger, Maikel B.G. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This research aimed at finding out the improvement of students’ vocabulary by using Last Man Standing Game at Seventh grade of SMP Kristen Malak. This research used pre-experimental design with one group pre-test and post-test. The population of this research was the SMP Kristen Malak. The sample of this research was the seventh grade students which consisted of 11 students. The researcher used format multiple choice and fill in the blank test as the instrument of this research. Based on the research findings, it showed that using Last Man Standing Game was effective to increase students’ vocabulary. It is proved by mean score of post-test. The mean score before and after treatment (35,63 became 65,09) with the t-test value was greater than t-table 13,97 > 1.812. The researcher concluded that using Last Man Standing Game could increase students’ vocabulary and could be one good technique in teaching vocabulary.